Inovasi Produk Pengrajin Gerabah di Dusun Jetis, Panjangrejo, Pundong Bantul Yogyakarta - Aqidah Asri Suwarsi; Julia Noermawati Eka Satyarini; Safaah Restuning Hayati; Aninta Gina Sharfina; Anisatun Anggraeni (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Panjangrejo is one of the Tourism Villages located in the east of Bantul Regency. Geographically, the location of this Tourism Village is very strategic because this Pottery Tourism Village is on one of the Parangtritis beach tourist routes, which is very crowded by tourists. Due to a lack of attention and support from the village government, the pottery craft of the Panjamgrejo tourism village is not as popular as the Kasongan village. The main problems faced by craftsmen include the stiff competition between pottery artisans, the lack of demand from outside the region due to limitations in marketing digital products (digital marketing), and the fulfillment of safe and attractive packaging. The method used in this service is the method of training and substitution of science and technology. The solution of product packaging that is still simple is overcome by procuring durable and attractive packaging boxes to increase product sales power and minimize product breakage. Also, the promotion of products that have not been run optimally is overcome by digital marketing training both through social media Instagram to Facebook ads with better internet signal support due to the availability of modems to facilitate online product marketing.